Theranostic Nanomedicine for Malignant Gliomas - d'Angelo, Michele; Castelli, Vanessa; Benedetti, Elisabetta; Antonosante, Andrea; Catanesi, Mariano; Dominguez-Benot, Reyes; Pitari, Giuseppina; Ippoliti, Rodolfo; Cimini, Annamaria (Frontiers in Bioengineering and Biotechnology, 2019)
Brain tumors mainly originate from glial cells and are classified as gliomas. Malignant gliomas represent an incurable disease, since recurrence in few months after surgery and chemotherapy is common and mortality has remained the same in the last decades. This is mainly due to the heterogeneity of malignant gliomas, indicating that a single therapy is not effective for all patients. In this regard the advent of theranostic nanomedicine, a combination of imaging and therapeutic agents represents a strategic tool for the management of malignant brain tumors, enabling to meet therapies to the patient and avoiding overdosing the non-responders Here recent theranostic nanomedicine approaches for gliomas therapy are described.